Management of the engineering data for manufacturing - ATAKÖK, GÜRCAN (My University, 2021)
Most companies have adopted the use of computer integrated engineering software to cope with the increasing competition and pressure to produce better quality and at a faster rate, enhancing their systems on this basis. Models are designed on computers, designs are validated in the software, and tool paths for manufacturing are generated in different specific software. All engineering information is generated and stored in computers. This development enhances faster rate of works in companies; however, some problems such as the management of the data arise. All departments in a business work separately, but for the same purpose. It is required for each department to have access to related information. The existence of a system in which the information is checked and managed depending on their creation time, versions, and the department is of importance. In this article, a system that allows not only the mechanical design department, but also the manufacturing, storage, process planning, quality control, electrical design, purchasing departments, etc. to have access to the required information has been developed. In the absence of this kind of system, loss of time, scraps and loss of engineering time would be investigated. After starting up the system, its benefits are defined. Tracing the workflows for management purposes would be handled by the system. A 'Validation of Design' process is modelled for the company. The information can be accessible to only those responsible for the data, and not anyone else. This allows users to work in a better environment, hence, increases productivity.
Keywords: Makina Mühendisliği; Konstrüksiyon ve İmalat; Bilgisayar Destekli Tasarım ve İmalat; Mühendislik ve Teknoloji; Mechanical Engineering; Construction and Manufacturing; Computer Aided Design and Manufacturing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Automotive Engineering; Computational Mechanics; Physical Sciences; Concurrent engineering; Industry 4.0; Product data management; Product life cycle management